Crisis and recovery in Argentina: labor market, poverty, inequality and pro-poor growth dynamics - Melanie Khamis (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2005)
This paper explores the labor market, poverty, inequality and pro-poor growth dynamics in the recent economic crisis and recovery in Argentina. In the labor market it is possible to see the diverging experience of the economic crisis and recovery. For instance, the unemployed were more likely to find employment in the informal sector than in the formal sector. In terms of economic sectors it seems that certain labor-intensive, dynamic, low-skilled sectors such as manufacturing, other services, construction and retail contributed most to the movement between the different labor force states of employment, unemployment and inactivity. Policy responses in the labor market to poverty and inequality increases from the economic crisis were implemented through government transfers, in particular the workfare program Plan Jefes y Jefas. The pro-poor features of the early economic recovery period were mainly accounted for by these government transfers. However, at later stages of recovery income increases of the poor are less attributed to government transfers and more due to the pro-poor pattern of growth itself.
Keywords: I30; I38; J40; O49; 330; Wirtschaftswachstum; Wirtschaftskrise; Arbeitsmarkt; Einkommensverteilung; Armut; Argentinien